Association of CD209 (DC-SIGN) rs735240 SNV with paucibacillary leprosy in the Brazilian population and its functional effects - Germano, Giovanna Valle [UNESP]; Braga, André Flores [UNESP]; Camargo, Rodrigo Mendes de [UNESP]; Ballalai, Priscila Betoni; Bezerra, Ohanna Cavalcanti; Manta, Fernanda Saloum de Neves; Belone, Andréa de Faria Fernandes; Soares, Cleverson Teixeira; Das, Pranab Kumar; Moraes, Milton Ozório; Latini, Ana Carla Pereira; Souza, Vânia Niéto Brito de (FapUNIFESP (SciELO), 2022)
BACKGROUND Leprosy, caused by Mycobacterium leprae, is a public health problem in Brazil that affects peripheral nerves, resulting in physical disabilities. During host-pathogen interactions, the immune response determines leprosy outcomes from a localised (paucibacillary) form to a disseminated (multibacillary) form. The recognition of M. leprae involves the DC-SIGN receptor, which is present on the dendritic cells (DCs) and participates in immune activation. OBJECTIVES To evaluate the association of polymorphisms in the promoter region of the gene encoding DC-SIGN (CD209) and the clinical form of leprosy, and to investigate its functional effects. METHODS The study population included 406 leprosy patients from an endemic area in Brazil [310 multibacillary (MB); 96 paucibacillary (PB)]. A functional evaluation based on the effects of the single nucleotide variant (SNV) associated with PB leprosy on the specific immune response was also performed. RESULTS The GA genotype and the presence of the A allele of rs735240 (-939G>A) were associated with PB leprosy [OR: 2.09 (1.18-3.69) and 1.84 (1.07-3.14), respectively]. Carriers of the A allele showed reduced expression of CD209 and TGF-β1 in leprosy lesions in comparison with individuals with GG genotype, in addition to a higher response to the Mitsuda test. CONCLUSION These data suggest that rs735240 influences the immune response against M. leprae and clinical presentation of leprosy.
Keywords: DC-SIGN; leprosy; Mycobacterium leprae; single nucleotide polymorphism